Challenges of the Nurse Manager in Implementation of Evidence-based Nursing Practice (EBNP) - Rachmawati, Anita; Hartiti, Tri; Fajrin, Ela; Puteri, Fauzizah; Nabila, Amelia (Universitas Muhammadiyah Semarang, 2023)
Evidence-based practice (EBP) is a nursing concept to improve the quality of health services. Many educational institutions have produced nursing research, but its application in nursing service practice has not been optimal because many nurses have not been exposed to that research. This research aims to find out the challenges of nurse managers in implementing evidence-based nursing practice (EBNP). The method used in this study is the qualitative method by conducting a Forum Group Discussion (FGD) with the five heads of rooms at RSJD Dr. Amino Gondohutomo Central Java Province regarding how to apply EBNP in providing health services. Based on the results of the FGD shows that although the application of EBNP is necessary to increase the knowledge, skills, and competencies of nurses so that innovations emerge in the provision of nursing care, there are still internal and external obstacles that hinder the implementation of EBNP. In the future, to be able to provide excellent patient care decisions, EBNP is needed for making appropriate clinical decisions based on existing cases.